China and the WTO: Why multilateralism still matters, by André Sapir and Petros C. Mavroidis, eds. - GAO, Henry S. (Institutional Knowledge at Singapore Management University, 2022)
This timely book addresses the most important problem facing the WTO: the challenge of the unique economic model of China, the largest emerging economy in the world. Penned by a leading trade lawyer and a leading trade economist, the book provides an excellent account of the legal rules with a firm grounding in economic analysis. Starting with an overview of China’s economic reform and its accession to the GATT and then the WTO, the book notes how China’s integration into the global trading system has been propelling its phenomenal economic growth. At the same time, however, its rise has led to increasing frictions with other trade partners, due to the inherent conflicts between its “socialist market economy”, the relative decline of the West, and the inability of the WTO to upgrade its rules and the resulting “regulatory stalemate”. These clashes led to a plethora of complaints against China, with those against state-owned enterprises and forced technology transfer as two prime examples. The book discussed attempts to address these problems, by drawing lessons from existing WTO jurisprudence, China’s accession protocol, and how the GATT and WTO has dealt with non-market economies in the past. After concluding that the past does not provide useful lessons, the book moves on to discuss future options. It rejects both the unilateral “stick” approach employed by US President Donald Trump, as well as the overly-accommodating “carrot” approach advocated by famed Harvard economist Dani Rodrik. Instead, it suggests a multilateral solution through creating new rules at the WTO, drawing heavily from recent rule-making efforts in other fora such as the CPTPP and the new plurilateral initiatives.